Comparative analysis of hard winter wheat seeds damage with different germ morphotype - A. G. Galayan; A. V. Bondarev (Новые технологии, 2022)
Seeds with a certain embryo shape have a variation in germination, some are more productive, others are not. This phenomenon has become the impetus for the systematization of seed groups by embryos. We have identified 8 groups (1a, 1, 2, 3, 4, 5, 6, 7, 8), there are strong and weak seeds structured according to this hierarchy. One of the problems of vegetation and the formation of the desired crop is the impact of factors that are regulated. The seed material is heterogeneous and, therefore, its development is unpredictable. Seeds of any agricultural crop, no matter whether it is a variety or a hybrid, have external and internal properties and signs that affect the stability of their ontogenesis. The economic and biological qualities of seeds depend on the genetic characteristics of the variety obtained as a result of breeding. The external qualities of seeds characterize the properties of seeds, which are determined by the adaptive landscape component, agrotechnology of cultivation and the equipment used. Yield losses are difficult to control and it is important to reduce. The yield is affected not only by their initial biological potential, but also by the further mechanical impact of agricultural machinery from pre-sowing treatment to sowing. The purpose of the research is to assess the damage of the seed material by various mordants. The objectives of the research are the preliminary systematization of winter hard wheat grains by the germ morphotype, as well as further pre-sowing processing by various machines. The objects of the study are winter hard wheat grains and picklers PNSh-3, PKS-20, PS-10A, PNU-4, mixer-inlay «EcoMix-5». As a result of the research, the most productive varieties of winter hard wheat (Amazonka (8.32 t/ha) have been identified, Kristella (8.27 t/ha), Yantarina (8.07 t/ha), Yakhont (7.81 t/ha)) and the EcoMix-5 device with the least damage to seeds during their pre-sowing treatment.